Audience consumption motives on online celebrity gossip account’s contents - Prawadika Aji, Angga; Astari, Mariska Dyah (Universitas Padjadjaran, 2023)
Background: The presence of the Internet has introduced a more complex way within the process of disseminating various images and information about celebrities, including private celebrity information such as scandals, conflicts, and various aspects of personal life that previously could only be enjoyed in classic infotainment formats in the mass media. Purpose: This study analyzes the motives of the audience’s consumption process for the content produced by various celebrity gossip accounts in Indonesian cyberspace. This research aims to dig deeper into the audience’s motives when consuming this particular information about celebrities. Methods: This research was conducted using in-depth interviews with ten sources who regularly consume the content of online celebrity gossip accounts on social media. Results: The results show that three motives encourage audiences to consume celebrity gossip online: informational motives, entertainment motives, and social motives. The information motive refers to the interviewee’s perception that online celebrity gossip accounts provide a more detailed and exclusive source of information. The entertainment motive refers to the enjoyment of the audience when they are involved in ‘imaginary drama’ and heated debate between audiences in the comment section. Social motive refers to the value of celebrity gossip as a valuable resource to start conversations and maintain group cohesion among close friends. Conclusions: The public’s interest in consuming celebrity information, whether for informational, entertainment, or social reasons, indicates an unrelenting demand for information about celebrities which in turn encourages the proliferation of gossip-providing accounts on social media. Implications: This study itself serves as an initial stepping stone to open a more serious study on celebrity culture in Indonesia.